الاصابہ فی تمییز الصحابہ میں نماز و روزے سے متعلقہ روایاتِ اَحکام کا تحقیقی جائزہ: Research Review of the Traditions of Rulings on Prayer and Fasting in Al-Aṣābah Fī Tamīz al-Ṣaḥābah - Rashid, Majid (Al-Amīr Research Journal for Islamic Studies, 2020)
The book “Al-Aṣābah Fī Tamīz al-Ṣaḥābah” is a famous book of Ibn Ḥajar ‘Asqalānī on the life and contribution of the Companions. This book is quoted as a reference to decide the status of companions. It would not be wrong to call it the encyclopedia of the companions of the Holy Prophetﷺ. Apart from its status as a reference book regarding the companions this book encompasses the Seerah of Holy Prophet in a detailed and well composed manner. The distinction of the book is not hidden from the experts of science and research. In the book and other similar books, the life of the companions was discussed and the biography of the Prophet ﷺwas also described, but another aspect that remained unexplored in these books is the virtues and commandments mentioned in it. There are also narrations about virtues. In this paper the researcher has evaluated the Hadiths related to prayer and fasting that are narrated in Al-Aṣābah Fī Tamīz al-Ṣaḥābah. The evaluation comprises of authenticity of narrators and text, narrators’ mutual association or disassociation and the final decree about the authenticity of a hadith in the light of all available evidences.